Phantom ladies : Hollywood horror and the home front - Snelson, Tim, 1973- (Rutgers University Press, 2014)
Defying industry logic and gender expectations, women started flocking to see horror films in the early 1940s. The departure of the young male audience and the surprise success of the film Cat People convinced studios that there was an untapped female audience for horror movies, and they adjusted their production and marketing strategies accordingly. Phantom Ladies reveals the untold story of how the Hollywood horror film changed dramatically in the early 1940s, including both female heroines and female monsters while incorporating elements of "women's genres" like the gothic mystery. Drawing from a wealth of newly unearthed archival material, from production records to audience surveys, Tim Snelson challenges long-held assumptions about gender and horror film viewership. Examining a wide range of classic horror movies, Snelson offers us a new appreciation of how dynamic this genre could be, as it underwent seismic shifts in a matter of months. Phantom Ladies, therefore, not only includes horror films made in the early 1940s, but also those produced immediately after the war ended, films in which the female monster was replaced by neurotic, psychotic, or hysterical women who could be cured and domesticated. Phantom Ladies is a spine-tingling, eye-opening read about gender and horror, and the complex relationship between industry and audiences in the classical Hollywood era